Systemic Nickel Allergy Syndrome: Nosologic Framework and Usefulness of Diet Regimen for Diagnosis. (July 2013) - Braga, M.; Quecchia, C.; Perotta, C.; Timpini, A.; Maccarinelli, K.; Di Tommaso, L.; Di Gioacchino, M.
Systemic (gastrointestinal and skin) reactions to ingestion of nickel rich foods in patients with nickel allergic contact dermatitis characterize Systemic Nickel Allergy Syndrome (SNAS). The objective of the study was to describe the nosologic framework of the syndrome and to compare sensibility and specificity for SNAS diagnosis between two different low nickel diets - BraMa-Ni and the usually prescribed list of forbidden foods - along with patient adherence to diet. One hundred forty-five patients with suspected SNAS (by history and benefit from nickel dietary restrictions) were selected and orally challenged with nickel for a definite diagnosis. Specificity and sensibility of the diets were calculated in relation to the results of nickel challenges. The nosologic framework of SNAS was deduced from the clinical pictures of 98 patients with positive nickel challenge and characterized essentially by skin and gastrointestinal symptoms, whereas all other symptoms (dizziness, headache etc.) were never elicited by the oral nickel challenge. The specificity and sensibility of BraMa-Ni in detecting SNAS were significantly higher than the forbidden food list diet, with an excellent patient adherence. Therefore, BraMa-Ni diet can be prescribed for the treatment of the syndrome other than for the diagnosis, the gold standard of which remains the oral nickel challenge.